Neotropical Species of Metaphycus (Hymenoptera, Encyrtidae) Parasitoids of Ceroplastes (Hemiptera, Coccidae): New Species, Interaction Records, and a Checklist - Tavares, M. T.; Santos, M. E. V.; Dal Molin, A.; Peronti, A. L. B. G. [UNESP]; Sousa-Silva, C. R. (Entomological Soc Brasil, 2019)
Parasitoids of Ceroplastes Gray were surveyed in the State of SAo Paulo, Brazil. Among the parasitoids reared, seven species of Metaphycus Mercet (Hymenoptera, Encyrtidae) were obtained. Metaphycusanaluciaesp. nov., M. floridensissp. nov., and M. grandissp. nov., are described as new species, and M. ceros Noyes, M. comes Noyes, M. dardanus Noyes, M. opis Noyes are recorded for the first time from Brazil. Ten new host-parasitoid associations are reported: M. analuciaesp. nov. parasitizing C. formicarius Hempel, C. glomeratus Peronti and C. iheringi Cockerel; M. ceros parasitizing C. cirripediformis Comstock; M. comes parasitizing C. formicarius; M. dardanus parasitizing C. glomeratus; M. floridensissp. nov. parasitizing C. floridensis; M. grandissp. nov. parasitizing C. grandis Hempel; and M. opis parasitizing C. glomeratus and C. janeirensis (Gray). A checklist of Metaphycus species associated with Ceroplastes, their distribution and host ranges are summarized and discussed.
Keywords: Ceroplastinae; Chalcidoidea; host-parasitoid interactions; parasitoid wasps; wax scale